Goal-Directed Fluid Therapy Using Normal Saline versus Ringer's Lactate in Pediatric Neurosurgical Patients: A Randomized Controlled Trial - Depuru, Aparna; Kaur, Kirandeep; Jangra, Kiran; Singla, Navneet; Bhagat, Hemant; Soni, Shiv Lal; Panda, Nidhi B.; Narayan, Vinitha; Prabhakar, Anuj (Journal of Neuroanaesthesiology and Critical Care, 2024)
Background Ringer's lactate (RL) and 0.9% sodium chloride (NS) are used intraoperatively in pediatric surgical patients. The fluid of choice in pediatric neurosurgical patients is still under research. Hence, we compared NS and RL intraoperatively with a primary objective of measuring the absolute difference in serum chloride concentrations (ΔCl-) after surgery from baseline. Secondary objectives included changes in other electrolytes, osmolarity, pH, creatinine, brain relaxation score (BRS), and neurological outcome at discharge using a modified Rankin scale (mRS).Methods This prospective randomized trial was conducted in American Society of Anesthesiologists status I to II children, aged 6 months to 14 years, after Institutional Ethical Committee approval and written informed consent. Forty patients were randomized in group-S (received 0.9% Saline) and group-R (received RL). The fluid administration was guided by Pleth Variability Index (target <13%). Arterial blood samples were taken at the start of surgery, during tumor resection, and at the end of surgery.Results Twenty-one patients in NS and 19 patients in RL were enrolled. ΔCl- was 12 (9–16) mmol/L in NS group and 4 (2–15) mmol/L in RL group, p = 0.03. NS group developed more metabolic acidosis (6 [28.6%] vs. 0 [0.0%], p = 0.021). There was no difference in the other electrolytes, serum osmolarity, BRS, perioperative creatinine, and mRS between groups, p = 0.36, p = 0.096, p = 0.658, and p = 0.168, respectively.Conclusion Intraoperative use of NS causes derangement in chloride balance, leading to metabolic acidosis compared to RL in children undergoing neurosurgical procedures. However, there was no difference in the other parameters, including serum osmolarity, BRS, and mRS.
Keywords: neurosurgery; normal saline; pediatric; Ringer's lactate